Photoluminescence and Judd–Ofelt analysis of Eu3+ doped LaAlO3 nanophosphors for WLEDs. (November 2015) - Manohar, T.; Naik, Ramachandra; Prashantha, S.C.; Nagabhushana, H.; Sharma, S.C.; Nagaswarupa, H.P.; Anantharaju, K.S.; Pratapkumar, C.; Premkumar, H.B.
Abstract: Europium doped lanthanum aluminate nanophosphors were synthesized by a combustion process using Oxalyl di-hydrazide as fuel. The nanophosphors calcined at 900 °C for 3 h were characterized by PXRD, FTIR spectroscopy, SEM and TEM. The average crystallite size determined by TEM and Scherrer's method was found to be in the range 20–50 nm. The characteristic emission peaks (λexi - 395 nm) recorded at ∼ 591, 616, 646 and 696 nm ( 5 D0 → 7 Fj=0, 1, 2, 3 ) may be attributed to the 4f–4f intra shell transitions of Eu 3+ ions. The estimated CIE chromaticity co-ordinates were calculated from emission spectra, were close to the national television standard committee value of red emission. Correlated color temperature was found to be 1929 K. Graphical abstract: Highlights: Nanophosphors of LaAlO3 : Eu 3+ – prepared by facile solution combustion technique. Characteristic emission peaks of Eu 3+ ion in the range 550–700 nm are recorded. CIE co-ordinate values lies in red region. LaAlO3 : Eu 3+ may be quite useful for display applications.